Impulsive noise pollution in the Northeast Atlantic: Reported activity during 2015–2017. (March 2020) - Merchant, Nathan D.; Andersson, Mathias H.; Box, Tetrienne; Le Courtois, Florent; Cronin, Dónal; Holdsworth, Neil; Kinneging, Niels; Mendes, Sónia; Merck, Thomas; Mouat, John; Norro, Alain M.J.; Ollivier, Benjamin; et al.
Abstract: Underwater noise pollution from impulsive sources (e.g. explosions, seismic airguns, percussive pile driving) can affect marine fauna through mortality, physical injury, auditory damage, physiological stress, acoustic masking, and behavioural responses. Given the potential for large-scale impact on marine ecosystems, some countries are now monitoring impulsive noise activity, coordinated internationally through Regional Seas Conventions. Here, we assess impulsive noise activity in the Northeast Atlantic reported during 2015–2017 to the first international impulsive noise register (INR), established in 2016 under the OSPAR Convention. Seismic airgun surveys were the dominant noise source (67%-83% of annual activity) and declined by 38% during 2015–2017. Reported pile driving activity increased 46%. Explosions and sonar/acoustic deterrent devices both had overall increases in reported activity. Some increases were attributable to more comprehensive reporting in later years. We discuss utilising the INR for risk assessment, target setting, and forward planning, and the implementation of similar systems in other regions. Highlights: Impulsive noise pollution can have a range of adverse impacts on marine fauna. Impulsive noise sources are now being monitored in the Northeast Atlantic. Data for 2015 onwards have been reported to an international impulsive noise registry. During 2015–2017, reported seismic airgun surveys decreased, pile driving increased. Some increases may be attributable to more comprehensive reporting in later years.